Analisis Peran Guru PAI dalam Upaya Meningkatkan Motivasi Belajar Siswa - Burhanuddin Chusnul Chuluq; Maryadi Maryadi (Jawda: Journal of Islamic Education Management, 2022)
Teachers have an important role in children's self-development by providing various kinds of knowledge and skills. So teachers are required to prepare various abilities in carrying out education and guidance to students by encouraging them to be independent in reaching maturity. The teacher's role can use various ways to generate learning motivation in students by doing: a) giving points, prizes, competitions, ego-involvement, giving tests, knowing results, praise, punishment, desire to learn, interests, and recognized goals. According to Abraham Maslow "Motivation is constant, never ending, fluctuant and complex, and that it is an almost universal characteristic af particulary every organism state of affairs". This definition from Abraham Maslow is interpreted by Fudyartanto, namely "motivation is constant (fixed), never ending, fluctuating and complex, and it is a universal characteristic of every activity of organisms.Referring to the educational philosophy of Empiricism put forward by the British philosopher, John Locke (1632-1704), he was a realist who believed that education occurred through real (empirical) experience. In line with the expression experience is the best teacher (experience is the best teacher), the application of empiricism in education, that educators are optimistic about being able to shape children by providing the desired experiences. SD Muhammadiyah 11 Mangkuyudan Surakarta by using a qualitative approach, from the results of the study it was found that teachers had carried out their duties well but there were still factors inhibiting the learning motivation of grade VI students at SD Muhammadiyah 11 Surakarta including: Lack of student willingness to learn, Lack of attention from parents, Factors of educators, association, community environment.